William Goode (1801-1868) - Stevener, Crawford M., author.
1 online resource (271 pages).
Keywords: This book examines the theology of William Goode (1801-1868), a leading Church of England theological polemicist in the nineteenth century. During exceedingly turbulent periods for the Church of England, William Goode was the foremost historical scholar who consistently rose to the occasion to write in defence of the church's reformed and protestant nature. His position as the pre-eminent refuter of Tractarian theology is developed and interpreted contextually in this volume. Through a meticulous reading of all of Goode's original works, relevant Victorian newspapers and journals, as well as surviving manuscript evidence, a full picture of Goode's theology in his nineteenth-century context is delineated. Goode's writing on successive doctrinal topics is examined in the context of theological crises besieging the Church of England and analysis of his corpus is demonstrated to be important for considering both reactions to the Oxford Movement and Anglican evangelical theology. The chapters consider Goode's role in ecclesiastical judicial settings, his defence of the Protestant nature of the Church of England as legally established in the Reformation, and his evangelical Anglican interpretation of the English formularies. This book is valuable reading for scholars of Church history and religious history, particularly those with an interest in the Oxford Movement, Anglicanism, Evangelicalism, and the Reformation.